The Fetal Allograft Revisited: Does the Study of an Ancient Invertebrate Species Shed Light on the Role of Natural Killer Cells at the Maternal-Fetal Interface?. (17th June 2008) - Lightner, Amy; Schust, Danny J.; Chen, Yi-Bin A.; Barrier, Breton F.
Abstract : Human pregnancy poses a fundamental immunological problem because the placenta and fetus are genetically different from the host mother. Classical transplantation theory has not provided a plausible solution to this problem. Study of naturally occurring allogeneic chimeras in the colonial marine invertebrate, Botryllus schlosseri, has yielded fresh insight into the primitive development of allorecognition, especially regarding the role of natural killer (NK) cells. Uterine NK cells have a unique phenotype that appears to parallel aspects of the NK-like cells in the allorecognition system of B. schlosseri. Most notably, both cell types recognize and reject "missing self" and both are involved in the generation of a common vascular system between two individuals. Chimeric combination in B. schlosseri results in vascular fusion between two individual colonies; uterine NK cells appear essential to the establishment of adequate maternal-fetal circulation. Since human uterine NK cells appear to de-emphasize primary immunological function, it is proposed that they may share the same evolutionary roots as the B. schlosseri allorecognition system rather than a primary origin in immunity.